Treatment of cystic thyroid nodes through a combination of sclerotherapy and laser interstitial thermotherapy - A. V. Shydlovscky (Kazimierz Wielki University, 2015)
Shydlovscky A. V. Treatment of cystic thyroid nodes through a combination of sclerotherapy and laser interstitial thermotherapy. Journal of Education, Health and Sport. 2015;5(4):41-51. ISSN 2391-8306. DOI: 10.5281/zenodo.16592 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A41-51 https://pbn.nauka.gov.pl/works/553133 http://dx.doi.org/10.5281/zenodo.16592 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 15.03.2015.   UDC 616.441-006.2-089.19/-085.849.19   Treatment of cystic thyroid nodes through a combination of sclerotherapy and laser interstitial thermotherapy   A. V. Shydlovscky   «Ternopil I. Ya. Horbachevskyi State Medical University of the Ministry of Healthcare of Ukraine»   Abstract The technology of cystic nodular goiter treating with the volume of liquid component from 20 to 80 % using a combination of sclerotherapy by ethanol (SE) and laser interstitial thermotherapy (LITT). At the beginning, we performed the complete obliteration of the cyst cavity connective tissue by the SE, and LITT for effecting on tissue component node. We used 70 % ethanol solution and diode laser with a wavelength of 1060 nm, power 2,8-3,2 watts. The dynamics of follow - SE cysts cavity, and after LITT - the tissue component node gradually, respectively, 6 and 9 months transformed into connective tissue. The slowdown in the process of reduction of cysts or tissue site during these periods and of nodular parenchyma cells considered indications for redo SE or LITT. In all 109 patients the treatment proved to be effective - cystic node transformed to connective tissue. Contraindications to the use of a combination CE and LITT had hypothyroidism, autoimmune thyroiditis, multinodular goiter volume of tissue component unit more than 60 % by volume of particles gland or multycyst transformation of nodules. Pathological influence of SE or LITT for the structure of paranodular parenchyma and parenchyma of the gland and its function is not found. After 3 years after treatment in 87 patients studied changes in the structure, function and thyroid volume and hem in place node were observed. Key words: cystic nodular goiter, treatment, sclerotherapy with ethanol, laser thermotherapy.